The Effects of Various Parameters on Cr (VI) Adsorption by Raw Rice Husk - Subramaniam, P.; Khan, N.A.; Ibrahim, S. (Faculty of Science, University of Malaya, 2006)
The effects of pH, contact time and adsorbent concentration on the adsorption of Cr (VI) onto raw rice husk have been investigated. The parameters - raw rice husk (RRW) particle size which was in the range of 450-600 Âµm, concentration from 10g/1 to 70g/1, contact time 0.5 to 2.0 hours, and pH 1-8 were tested using 50mg/1 solutions of Cr (VI). The maximum removal efficiency was 66.6% for RRW concentration of 70g/1, at pH 2 and 2 hours contact time. In terms of adsorption capacity, the 10g/1 adsorbent concentration gave the highest reading of 2.2 mg/g for a pH of 2 and 2 hours contact time.